2006
DOI: 10.1097/01.ta.0000226154.38852.e6
|View full text |Cite
|
Sign up to set email alerts
|

Spiral Computed Tomography for the Initial Evaluation of Spine Trauma: A New Standard of Care?

Abstract: SCT is a more rapid and sensitive modality for evaluating the spine compared with PFR and is obtained at a similar cost. The advantages of SCT suggest that this readily available diagnostic modality may replace PFR as the standard of care for the initial evaluation of the spine in trauma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(72 citation statements)
references
References 36 publications
(37 reference statements)
1
69
0
2
Order By: Relevance
“…CT with low-radiation dose has been recently shown to be a reliable method in the assessment of pedicle screw placement with substantial interobserver and intraobserver agreements [6]. Furthermore, the radiation dose of plain radiography of spine varies in different reports and in some studies is reported to be as high as 26 mSv [7] compared with 0.37 mSv for the low-dose spine CT in that study [6]. The risk for development of lethal cancer is calculated to be 5% per Sievert [8].…”
Section: Introductionmentioning
confidence: 99%
“…CT with low-radiation dose has been recently shown to be a reliable method in the assessment of pedicle screw placement with substantial interobserver and intraobserver agreements [6]. Furthermore, the radiation dose of plain radiography of spine varies in different reports and in some studies is reported to be as high as 26 mSv [7] compared with 0.37 mSv for the low-dose spine CT in that study [6]. The risk for development of lethal cancer is calculated to be 5% per Sievert [8].…”
Section: Introductionmentioning
confidence: 99%
“…CT screening has a higher sensitivity and specificity for evaluating cervical spine injury compared with plain film radiographs [25,27,28]. In the cervical spine, CT detects 97-100% of fractures, but its accuracy in detection of purely ligamentous injuries has not been documented [23].…”
Section: (Multidetector) Computed Tomographymentioning
confidence: 99%
“…An additional advantage is that CT allows more rapid radiological clearance of the cervical spine than radiography [27,28]. For these reasons, many major trauma centers nowadays have replaced plain film radiographs with spiral CT or MDCT as the standard of care in the initial evaluation of the cervical spine in moderate to severe trauma patients [27].…”
Section: (Multidetector) Computed Tomographymentioning
confidence: 99%
See 2 more Smart Citations